2020
DOI: 10.1177/2050640620937593
|View full text |Cite
|
Sign up to set email alerts
|

Colon capsule endoscopy versus CT colonography after incomplete colonoscopy. Application of artificial intelligence algorithms to identify complete colonic investigations

Abstract: Background Guidelines suggest computed tomography colonography (CTC) following incomplete optical colonoscopy (OC). Colon capsule endoscopies (CCE) have been suggested as an alternative, although completion rates have been unsatisfactory. Introduction of artificial intelligence (AI)-based localization algorithms of the camera capsules may enable identification of incomplete CCE investigations overlapping with incomplete OCs. Objective The study aims to investigate relative sensitivity of CCE compared with CTC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 25 publications
(64 reference statements)
0
33
0
1
Order By: Relevance
“…The above results are consistent with most other complication rates after treatment with laparoscopy combined with duodenoscope for treatment of gallbladder stones combined with common bile duct stones [4,5,[26][27][28], providing support for laparoscopy combined with duodenoscope in the treatment of gallstones. Of course, AI-assisted visual sensing technology shows a wide range of applications, not just for assisted endoscopic treatment of gallbladder stones, which has been illustrated in a number of studies on the optimization of colonoscopy bowel preparation and the establishment and preliminary verification of the artificial intelligence-assisted colorectal polyp identification system [29][30][31][32]. AI-assisted visual sensing technology can also be used to prevent and control children's myopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results are consistent with most other complication rates after treatment with laparoscopy combined with duodenoscope for treatment of gallbladder stones combined with common bile duct stones [4,5,[26][27][28], providing support for laparoscopy combined with duodenoscope in the treatment of gallstones. Of course, AI-assisted visual sensing technology shows a wide range of applications, not just for assisted endoscopic treatment of gallbladder stones, which has been illustrated in a number of studies on the optimization of colonoscopy bowel preparation and the establishment and preliminary verification of the artificial intelligence-assisted colorectal polyp identification system [29][30][31][32]. AI-assisted visual sensing technology can also be used to prevent and control children's myopia.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the mean intersection ratio, the more accurate the segmentation algorithm. Its calculation expression was given as equation (30).…”
Section: Journal Of Sensorsmentioning
confidence: 99%
“…If optical colonoscopy is not possible, a colon capsule endoscopy or CT colonography may be performed. In a clinical trial, Deding et al found that the sensitivity of colon capsule endoscopy (estimated location by AI) following an incomplete optical colonoscopy was superior to CT colonoscopy, and the relative sensitivity of colon capsule endoscopy compared with CT colonography was 2.67 for polyps >5 mm and 1.91 for polyps >9 mm [ 103 ].…”
Section: Colon Cancer and Polypsmentioning
confidence: 99%
“…Knowing the location of the capsule, even an incomplete CCE may complete an incomplete colonoscopy investigation as long as it captures the most proximal point of the previous conducted attempt. Deding et al [ 1 ] underlined this clinical importance of a localization algorithm that is able to estimate the whereabouts of the capsule.…”
Section: Introductionmentioning
confidence: 99%
“…Solving for d in Equation ( 2) and substituting into Equation (1) gives the distance traveled between times t and t + 1 as a function of the intestine geometry, namely the radius R, and the angles for the projection of P at these times:…”
mentioning
confidence: 99%